Aqueous synthesis of L-cysteine-modified cobalt-doped zinc selenide/zinc sulfide quantum dots with enhanced fluorescence. Issue 5 (27th May 2020) - Huang, Meijing; Fang, Xiuting; Qiu, Chunhong; Huang, Fenghua
Abstract: Cobalt-doped zinc selenide/zinc sulfide quantum dots have been successfully synthesized directly in aqueous solution by using L-cysteine as the modifier. The optical properties and structures of the as-prepared quantum dots have been characterized through transmission electron microscopy, X-ray powder diffraction, infrared spectrum, energy dispersive X-ray spectrum, ultraviolet-visible spectrum, and fluorescence spectrum. The results show that cobalt-doped zinc selenide/zinc sulfide quantum dots are spherical particles with a diameter around 2.8 nm, have good dispersity and have a cubic zinc blende structure. The effects of several synthesis conditions on the fluorescence properties of the as-prepared quantum dots are surveyed and the optimum synthesis conditions are found to be as follows: reaction solution pH of 10.0; molar ratio of L-cysteine to hydrogen selenide ions to zinc ions of 1.6:0.15:1; doping content of cobalt ions of 2%; molar ratio of shell (zinc sulfide) to core (cobalt-doped zinc selenide) of 1.5:1. The fluorescence quantum yield of the as-prepared quantum dots increases from 6.4% to 19% via doping with cobalt ions and the epitaxial growth of zinc sulfide shell. The L-cysteine modified on the surface of cobalt-doped zinc selenide/zinc sulfide quantum dots renders the quantum dots water-soluble and bioconjugation capable. The L-cysteine-modified cobalt-doped zinc selenide/zinc sulfide quantum dots will have potential applications in biological fluorescence analysis.